Valuing Water Quality Improvement in China : A Case Study of Lake Puzhehei in Yunnan Province - Wang, Hua; Shi, Yuyan; Kim, Yoonhee; Kamata, Takuya (Elsevier, 2013)
Even though surface water has been polluted almost everywhere in China, few economic valuation studies have been conducted to value water quality changes. This paper reports an economic valuation study conducted in Yunnan, China, which estimates the total value of a real investment project to improve the water quality of Lake Puzhehei by one grade level. Located in Qiubei County far from big cities, the lake has been experiencing rapid water quality deterioration in past several years. Based on the multiple bounded discrete choice approach, an average household in Qiubei County is estimated to be willing to pay 30 yuan per month continuously for 5 years for the water quality improvement by one grade level, roughly equivalent to 3% of the average household income. The elasticity of willingness-to-pay with respect to income is estimated to be 0.21. The economic rate of return of the proposed project is estimated to be 18%, indicating an economically favorable investment in water quality improvement. This study also demonstrates that the previous knowledge about the water quality changes and about the project can have significant positive impacts on people's willingness to pay, whereas the interviewer effect on valuation can be negative.